Training and Assistance in Construction of Solar Cell Technology to Develop Community’s Knowledge about Renewable Energy in Ujan Mas Village, Muara Enim, South Sumatra - Muhammad Rendana; Yandriani Yandriani; Stevanus N. Jati; Puteri K. Wardhani; M. Ilham Fattullah; Rizqy M. Kusuma; Alifian A. A. Sonianto (To Maega : Jurnal Pengabdian Masyarakat, 2023)
The community development program is a prominent activity to identify and overcome local issues within community. The training and assistance program for solar cell technology application is useful to improve knowledge of community in Ujan Mas village, Muara Enim Regency, South Sumatra. The objective of this activity is to transfer knowledge of solar cell technology starting from construction to application process. The tehnique used in this community service program is the locality development approach. This activity conducted for two days (3-4 September 2022). This activity resulted in enhancing the community’s knowledge of implementing solar cell technology with a 92% understanding rate, and also reducing electrical bill of community. In addition, this activity is one of a way to support the Indonesian government program to build an eletrical independent village or city. For future community development activities, we suggest to give a training program for other green energies such as biogas which used domestic and agricultural wastes to produce eletricity.